2003
DOI: 10.1016/j.pain.2003.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic analysis of sex differences in opioid antinociception in rats

Abstract: Sex differences in opioid antinociception have been reported in rodents and monkeys, with opioids being more potent in males than females. In the present study, the influence of rat strain on sex differences in opioid antinociception was examined in a warm water tail-withdrawal procedure. Antinociceptive tests were conducted with the high-efficacy micro-opioid morphine, and the less efficacious opioids buprenorphine, butorphanol and nalbuphine. Baseline nociceptive latencies were consistently higher in males t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
49
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 30 publications
6
49
3
Order By: Relevance
“…This contrasts with reports (Cook et al, 2000;Terner et al, 2003) that a sex difference is more evident with lower efficacy -opioids. However, although Terner and colleagues also used the rat tail-withdrawal assay, they compared very low efficacy compounds, namely, buprenor- phine, butorphanol, and nalbuphine with morphine, and this may explain the discrepancy with the present findings.…”
Section: Discussioncontrasting
confidence: 88%
“…This contrasts with reports (Cook et al, 2000;Terner et al, 2003) that a sex difference is more evident with lower efficacy -opioids. However, although Terner and colleagues also used the rat tail-withdrawal assay, they compared very low efficacy compounds, namely, buprenor- phine, butorphanol, and nalbuphine with morphine, and this may explain the discrepancy with the present findings.…”
Section: Discussioncontrasting
confidence: 88%
“…Previous studies comparing opioid agonists that vary in efficacy also support the hypothesis that differential opioid receptor density underlies sex differences in opioid antinociception. Picker and colleagues have demonstrated that sex differences in opioid antinociception increase in magnitude as the efficacy of the agonist decreases [4,11,52]. Because low to intermediate efficacy agonists must activate more receptors than high efficacy agonists to produce antinociception, the functional significance of small sex differences in opioid receptor density would be magnified when testing lower efficacy agonists.…”
Section: Discussionmentioning
confidence: 99%
“…The primary factor among these is genotype. Studies in mice 21,[30][31][32] and rats [32][33][34][35][36] have demonstrated that sex differences in pain and analgesia can be demonstrated in certain strains but not others. The effects of gonadal hormones on pain-related traits are similarly strain-dependent 21,37 .…”
Section: Male Onlymentioning
confidence: 99%